UJI DAYA TERIMA TEMPE BIJI KECIPIR BERAS MERAH DAN KANDUNGAN GIZINYA - fera nababan (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2012)
Tempe is one of fermented food product which rich in protein. Tempe that we know so far is tempe made ​​from soybeans. One of ingredient that can be used as an alternative ingredient is winged bean, it contains protein which is equal to soybeans. The type of this research is experiments. The purpose of this research is to know acceptable the winged bean tempe with the addition of red rice based on taste, flavor, color, and texture are tested through a hedonic test and to know protein content in winged bean tempe with the addition of red rice. Methods of data analysis used barlett test and analysis of variance test. These results of this research showed that by organoleptic test of taste , colour and texture, winged bean tempe with addition 30% red rice is the most favorite by the panelist . The result from laboratoric test showed that protein content in winged bean tempe with addition red rice respectively decreased 2.39 g, 2.07 g and 2.28 g. Based on the analysis of variance, the addition of red rice with a variety of different influences that have real impact on taste, flavor, color and texture. Suggestion in this research that people use winged bean to make tempe, caused contains nutrition that body needed, for next research to eliminate unpleasant odors in the red rice winged bean tempe, and winged bean tempe with addition of red rice can be used as a source of protein and carbohydrates. Keywords: winged bean tempe, red rice, organoleptic attribute, acceptability test